Citizens as Partners: Information, Consultation and Public Participation in Policy-Making - OECD (Organisation for Economic Co-operation and Development, 2001)
This book examines a wide range of country experiences, offers examples of good practice, highlights innovative approaches and identifies promising tools (including new information technologies)for engaging citizens in policy making. It proposes a...